A systematic comparison of patient information leaflets from local and multinational pharmaceutical companies: Assessing content quality and completeness - Abdulaziz Ibrahim Alzarea; Azfar Athar Ishaqui; Muhammad Zeeshan; Abdullah Salah Alanazi; Aseel Awad Alsaidan; Tauqeer Hussain Mallhi; Muhammad Salman; Yusra Habib Khan; Javeria Farooq; Hassan H. Alhassan; Sami I. Alzarea; Omar Awad Alsaidan (PLoS ONE, 2025)
Background It is necessary to provide essential information to patients regarding medication to ensure safe and effective use. Patient Information Leaflets (PILs) are vital to fulfil this purpose. However, disparities in quality between multinational and local pharmaceutical companies PILs have been observed. The study aimed to assess and compare the completeness and quality of PILs available in community pharmacies from multinational and local pharmaceutical companies. Method A cross-sectional comparative study design was used for evaluating 695 PILs (312 multinational, 383 local) across various therapeutic classes (antibiotics, anti-hypertensives, anti-diabetics, NSAIDs, and antidepressants). PILs were assessed against 31 criteria encompassing general information, dosage, indications, administration, interactions, safety information, pharmacokinetics, toxicology, storage, adverse effects, and pregnancy/breastfeeding details. Descriptive statistics, t-tests, chi-square tests, and odds ratios were included in statistical analysis. Result Several criteria results showed excelling of Multinational PILs over local PILs. Significant differences favouring multinational PILs were observed in providing information on inactive ingredients (p = 0.024), adult-specific dosing (p = 0.0001), renal and hepatic dose adjustments (p = 0.018, p = 0.007 respectively), dosing in haemodialysis patients (p = 0.036), drug-drug interactions (p = 0.029), black box warnings (p = 0.027), clinical effects of toxicity (p = 0.045), and reporting adverse drug reactions (p = 0.04). Conclusion Multinational and local PILs, both performed well in providing basic information on active ingredients, brand names, contraindications, pregnancy, and lactation details. However, disparities among various aspects including inactive ingredient, specific dosing, dose adjusments and drug interactions between PILS of multinational and local pharmaceutical companies in Pakistan highlights the necessity for regulatory measures and industry initiatives to standardize PIL content. For ensuring patient safety and enhancing the quality of medication use it is essential to improve the comprehensiveness and clarity of PILs.